Efficacy and Safety of Varenicline for Smoking Cessation in Schizophrenia: A Meta-Analysis - Ahmed, Saeed; Virani, Sanya; Kotapati, Vijaya P.; Bachu, Ramya; Adnan, Mahwish; Khan, Ali M.; Zubair, Aarij; Begum, Gulshan; Kumar, Jeevan; Qureshi, Mustafa; Ahmed, Rizwan (Frontiers in Psychiatry, 2018)
Objective Smoking represents a major public health problem among patients with schizophrenia. To this end, some studies have investigated the efficacy of varenicline for facilitating smoking cessation in schizophrenia patients. The present review seeks to synthesize the results of these studies as well as document the reported side effects of using this medication. Methods An electronic search was performed using five major databases: PubMed, Scopus, EMBASE, Web of Science and Cochrane Library. Included in the current analysis were randomized clinical trials (RCTs) that have investigated the effect of varenicline in promoting smoking cessation in patients with schizophrenia. Risk of bias among included RCTs was assessed using the Cochrane Collaboration's quality assessment tool. Results Among the 828 screened articles, only four RCTs, which involved 239 participants, were eligible for meta-analysis. In patients with schizophrenia, varenicline treatment relative when compared to placebo significantly reduced the number of cigarettes consumed per day [SMD (95% CI) = 0.89(0.57-1.22)] and expired carbon monoxide levels [SMD (95% CI) = 0.50 (0.06-0.94)] respectively. Conclusion Despite the limited number of studies included in the meta-analysis, our results suggest that varenicline is an effective and safe drug to assist in smoking cessation in patients with schizophrenia. Future large-scale and well-designed RCTs are required to confirm this finding.